Microfluidic Formation of Double-Stacked Planar Bilayer Lipid Membranes by Controlling the Water-Oil Interface - Kan Shoji; Ryuji Kawano (Micromachines, 2018)
This study reports double-stacked planar bilayer lipid membranes (pBLMs) formed using a droplet contact method (DCM) for microfluidic formation with five-layered microchannels that have four micro guide pillars. pBLMs are valuable for analyzing membrane proteins and modeling cell membranes. Furthermore, multiple-pBLM systems have broadened the field of application such as electronic components, light-sensors, and batteries because of electrical characteristics of pBLMs and membrane proteins. Although multiple-stacked pBLMs have potential, the formation of multiple-pBLMs on a micrometer scale still faces challenges. In this study, we applied a DCM strategy to pBLM formation using microfluidic techniques and attempted to form double-stacked pBLMs in micro-meter scale. First, microchannels with micro pillars were designed via hydrodynamic simulations to form a five-layered flow with aqueous and lipid/oil solutions. Then, pBLMs were successfully formed by controlling the pumping pressure of the solutions and allowing contact between the two lipid monolayers. Finally, pore-forming proteins were reconstituted in the pBLMs, and ion current signals of nanopores were obtained as confirmed by electrical measurements, indicating that double-stacked pBLMs were successfully formed. The strategy for the double-stacked pBLM formation can be applied to highly integrated nanopore-based systems.